The effect of applying the blended learning model with the Moodle application on student cognitive improvement - Siswanto Siswanto; Zou Zhi-Hong; Markéta Bilanová (Universitas Negeri Yogyakarta, 2023)
This study aims to investigate the effect of implementing the blended learning model with Moodle application on improving students' cognitive abilities. Blended learning is a learning approach that integrates the use of digital technology and face-to-face interaction between teachers and students. Moodle is one of the popular e-learning platforms used in implementing blended learning. This study used a pre-test and post-test experimental control group design, where the research sample consisted of two groups of students, each of which was given different treatments: a control group and an experimental group. Students' cognitive data was measured through knowledge tests before and after treatment. Data analysis was performed using t-test and ANOVA. The results of this study are expected to provide useful information for educational institutions in choosing effective and efficient learning strategies to improve the quality of higher education.Â